Expression and identification of type 1 diabetes associated autoantigen IA-2 - 周文中 郑升 谢晓雁 杨键 李纪平 罗敏 贾秀娟 李果 陈战 许光武 谢超 张迪 (Chinese medical journal, 2003)
Objectives To obtain prokaryotic expressed IA-2 recombinant protein and to identify its immunological activity.Methods The complimentary DNA (cDNA) coding for the intracytoplasmic part of IA-2 (IA-2ic) was amplified from human fetal brain RNA, and was subcloned into the PinPoint Xa-1 T vector to construct recombinant expression plasmid, and was then expressed in E. coil JM109 cells as a fusion protein with a biotinylated peptide sequence at the aminoterminus. The biotinylated fusion protein was then purified by affinity chromatography and was subsequently dialyzed. Finally, its immunogenicity was evaluated by enzyme linked immunosorbent assay (ELISA).Results The purified IA-2ic fusion protein resolved on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) as a single Coomassie brilliant blue stained band with a molecular weight of 59 kDa and its immunogenicity was confirmed by ELISA.Conclusions E. coil expressed IA-2ic fusion protein has immunological activity. It can be used for detection of IA-2 autoantibodies (IA-2A) and for further studies on type 1 diabetes in future.